Nitrogen-doped carbon encapsulating molybdenum carbide and nickel nanostructures loaded with PVDF membrane for hexavalent chromium reduction - Yao, Y.; Hu, Y.; Yu, M.; Lian, C.; Gao, M.; Zhang, J.; Li, G.; Wang, Shaobin (Elsevier BV, 2018)
Molybdenum carbide and Ni 0 nanoparticles (NPs) embedding into N-doped carbon materials (Mo x Ni y @N-C) were prepared by one-step thermolysis of Ni, Mo, N, C precursors, and then loaded on poly (vinylidene fluoride) (PVDF) film to obtain the catalytic membranes (Mo x Ni y @N-C/PVDF). The membranes effectively catalyzed the reduction of toxic Cr VI to benign Cr III by employing formic acid (FA) as the reducing agent. The effects of parameters, such as initial concentrations of Cr VI (5–25 mg/L) and FA (0.117–0.702 M), solution pHs (2.12–5.43) and temperatures (15–55 °C), as well as HCOONa concentrations (0–0.20 M) on Cr VI reduction were analyzed in view of scalable industrial applications. Owing to the synergistic effects amongst Ni 0 , Mo x C, doped nitrogen, and oxygen groups as catalytic active sites, and carbon shell protection of metal NPs from leaching out, Mo x Ni y @N-C/PVDF catalysts exhibited excellent catalytic activity and recyclable capability for Cr VI reduction. The membrane's unique porous structure and large chemically active surface area not only minimize the NPs agglomeration, but also allow the facile transport of catalytic reactants to the active surface without suffering from high mass-transfer resistance. This study demonstrates Mo x Ni y @N-C/PVDF catalytic membranes with the morphological and structural features provide a green, economic, and fast method for the treatment of Cr VI containing waters.